Adhesion stabilized en masse intracellular electrical recordings from multicellular assemblies - Staufer, Oskar; Weber, Sebastian; Bengtson, C. Peter; Bading, Hilmar; Rustom, Amin; Spatz, Joachim P. (Nano letters, 2019)
Coordinated collective electrochemical signals in multicellular assemblies, such as ion fluxes, membrane potentials, electrical gradients, and steady electric fields, play an important role in cell and tissue spatial organization during many physiological processes like wound healing, inflammatory responses, and hormone release. This mass of electric actions cumulates in an en masse activity within cell collectives which cannot be deduced from considerations at the individual cell level. However, continuously sampling en masse collective electrochemical actions of the global electrochemical activity of large-scale electrically coupled cellular assemblies with intracellular resolution over long time periods has been impeded by a lack of appropriate recording techniques. Here we present a bioelectrical interface consisting of low impedance vertical gold nanoelectrode interfaces able to penetrate the cellular membrane in the course of cellular adhesion, thereby allowing en masse recordings of intracellular electrochemical potentials that transverse electrically coupled NRK fibroblast, C2C12 myotube assemblies, and SH-SY5Y neuronal networks of more than 200,000 cells. We found that the intracellular electrical access of the nanoelectrodes correlates with substrate adhesion dynamics and that penetration, stabilization, and sealing of the electrode-cell interface involves recruitment of surrounding focal adhesion complexes and the anchoring of actin bundles, which form a caulking at the electrode base. Intracellular recordings were stable for several days, and monitoring of both basal activity as well as pharmacologically altered electric signals with high signal-to-noise ratios and excellent electrode coupling was performed.
Gesehen am 10.03.2020